Народні уявлення та звичаєво-правові норми щодо наймитування в українських прислів’ях та приказках - Маліков, Василь Володимирович (Харківський національний університет ім. В. Н. Каразіна, 2012)
This paper offers the analysis of Ukrainian folk proverbs and sayings and shows their significance for customary law traditionsof wage labour. The case studied in the article concerns peasant concepts and norms about wage labour and the image of farm labourer in the second half of the XIX – the beginning of the XX centuries
Keywords: наймитування; традиційна народна культура; наймит; прислів’я; приказки